Cryphonectria carpinicola sp. nov. Associated with hornbeam decline in Europe. Issue 5 (May 2021) - Cornejo, Carolina; Hauser, Andrea; Beenken, Ludwig; Cech, Thomas; Rigling, Daniel
A bstract: Since the early 2000s, reports on declining hornbeam trees ( Carpinus betulus ) are spreading in Europe. Two fungi are involved in the decline phenomenon: One is Anthostoma decipiens, but the other etiological agent has not been identified yet. We examined the morphology, phylogenetic position, and pathogenicity of yellow fungal isolates obtained from hornbeam trees from Austria, Georgia and Switzerland, and compared data with disease reports from northern Italy documented since the early 2000s. Results demonstrate distinctive morphology and monophyletic status of Cryphonectria carpinicola sp. nov. as etiological agent of the European hornbeam decline. Interestingly, the genus Cryphonectria splits into two major clades. One includes Cry. carpinicola together with Cry. radicalis, Cry. decipiens and Cry. naterciae from Europe, while the other comprises species known from Asia—suggesting that the genus Cryphonectria has developed at two evolutionary centres, one in Europe and Asia Minor, the other in East Asia. Pathogenicity studies confirm that Car. betulus is a major host species of Cry. carpinicola . This clearly distinguished Cry. carpinicola from other Cryphonectria species, which mainly occur on Castanea and Quercus . Graphical abstract: Image 1 Highlights: A new species in the fungal genus Cryphonectria is described. Cryphonectria carpinicola has been found on declining hornbeam trees in Europe. Pathogenicity studies confirmed Carpinus betulus as a major host tree.